Glutathione Biosynthesis via Activation of the Nuclear Factor E2-Related Factor 2 (Nrf2) - Antioxidant-Response Element (ARE) Pathway Is Essential for Neuroprotective Effects of Sulforaphane and 6-(Methylsulfinyl) Hexyl Isothiocyanate - Keita Mizuno; Toshiaki Kume; Chie Muto; Yuki Takada-Takatori; Yasuhiko Izumi; Hachiro Sugimoto; Akinori Akaike (Elsevier, 2011)
Oxidative stress plays pivotal roles in aging, neurodegenerative disease, and pathological conditions such as ischemia. We investigated the effect of sulforaphane and 6-(methysulfinyl) hexyl isothiocyanate (6-HITC), a naturally occurring isothiocyanate, on oxidative stress-induced cytotoxicity using primary neuronal cultures of rat striatum. Pretreatment with sulforaphane and 6-HITC significantly protected against H2O2- and paraquat-induced cytotoxicity in a concentration-dependent manner. Sulforaphane and 6-HITC induced the translocation of nuclear factor E2-related factor 2 (Nrf2) into the nucleus and increased the expression of γ-glutamylcysteine synthetase (γ-GCS), a rate-limiting enzyme in glutathione synthesis, and the intracellular glutathione content. Treatment with reduced glutathione (GSH) and N-acetyl-l-cysteine, a substance for glutathione synthesis, significantly prevented the cytotoxicity induced by H2O2 and paraquat. Moreover, exposure to l-buthionine-sulfoximine, an irreversible inhibitor of γ-GCS, suppressed the protective effects of sulforaphane and 6-HITC. In contrast, sulforaphane and 6-HITC increased heme oxygenase-1 (HO-1) expression in neurons. However, zinc-protophorphyrin IX, a competitive inhibitor of HO-1, did not influence the protective effects of sulforaphane and 6-HITC. These results suggest that sulforaphane and 6-HITC prevent oxidative stress-induced cytotoxicity in rat striatal cultures by raising the intracellular glutathione content via an increase in γ-GCS expression induced by the activation of the Nrf2-antioxidant response element pathway. Keywords:: isothiocyanate, neuroprotection, oxidative stress, nuclear factor E2-related factor 2 (Nrf2)